Sarcopenia: Prevalence, and Impact on Operative and Oncologic Outcomes in the Multimodal Management of Locally Advanced Esophageal Cancer. Issue 5 (November 2017) - Elliott, Jessie A.; Doyle, Suzanne L.; Murphy, Conor F.; King, Sinead; Guinan, Emer M.; Beddy, Peter; Ravi, Narayanasamy; Reynolds, John V.
Abstract : Objective: The aim of this article was to study the prevalence and significance of sarcopenia in the multimodal management of locally advanced esophageal cancer (LAEC), and to assess its independent impact on operative and oncologic outcomes. Summary of Background Data: Sarcopenia in cancer may confer negative outcomes, but its prevalence and impact on modern multimodal regimens for LAEC have not been systematically studied. Methods: Two hundred fifty-two consecutive patients were studied. Lean body mass (LBM), skeletal muscle index (SMI), and fat mass (FM) were determined pre-treatment, preoperatively, and 1 year postoperatively. Sarcopenia was defined by computed tomography (CT) at L3 as SMI < 52.4 cm 2 /m 2 for males and SMI < 38.5 cm 2 /m 2 for females. All complications were recorded prospectively, including comprehensive complications index (CCI), Clavien-Dindo complication (CDC), and pulmonary complications (PPCs). Multivariable linear, logistic, and Cox regression analysis was performed. Results: In-hospital mortality was 1%, and CCI was 21 ± 19. Sarcopenia increased ( P = 0.02) from 16% at diagnosis to 31% post-neoadjuvant therapy, with loss of LBM (-3.0 ± 5.4 kg, P < 0.0001), but not FM (-0.3 ± 2.7 kg, P = 0.31) during treatment. On multivariable analysis, preoperative sarcopenia was associated with CCI ( P = 0.043), and CDC ≥IIIb ( P = 0.003). PPCs occurred in 36% nonsarcopenic versus 55% sarcopenic patients ( P = 0.01). Sarcopenia did not impact disease-specific ( P = 0.14) or overall survival ( P = 0.11) after resection. At 1 year, 35% had sarcopenia, significantly associated with pre-treatment BMI ( P = 0.013) but not complications ( P = 0.20). Conclusions: Sarcopenia increases through multimodal therapy, is associated with an increased risk of major postoperative complications, and is prevalent in survivorship. These data highlight a potentially modifiable marker of risk that should be assessed and targeted in modern multimodal care pathways. Abstract : Supplemental Digital Content is available in the text